Pattern of Road Traffic Accident Cases Attending in the Emergency Department of Khwaja Yunus Ali Medical College and Hospital, Bangladesh. - Yesmin, Laila; Islam, Md Rafiqul; Happy, Taslima Akber; Ali, Eleza; Ahmed, Farzana; Ghosh, Debasish; Yasmin, Ayesha (KYAMC Journal, 2022)
Objective: To evaluate the pattern of Road Traffic Accident cases attending the Emergency Department of Khwaja Yunus Ali Medical College & Hospital (KYAMCH), Enayetpur, Sirajganj. Materials and Methods: This cross-sectional study was carried out at the emergency department of Khwaja Yunus Ali Medical College and hospital (KYAMCH), Enayetpur, Sirajganj from January’21 to June’21. Total 148 Road Traffic Accident (RTA) cases were collected by using a pre-designed format from the Emergency register/ records book, for the study. Results: During the study majority of the cases (73.65 %) were male and 58 (39.19%) of the patients belong to above 40 years of age, In the above 40 age group (29.73%) were male and (9.45%) were female. The majority (29.05%) had only soft tissue injury (Abrasion/Bruise/Laceration), followed by (27.02%) had only lower limb fracture and dislocation, (17.58%) of patient had only upper limb Fracture and dislocation,( 19.59%) had head injury,( 4.05%) had both upper and lower limb fracture, only (1.35%) had spinal cord injury and (1.35%) had another injury. During the accident common vehicle for the accident was Compressed Natural Gas (CNG) Auto-rickshaw (28.38%) followed by Motorcycle were (22.97%), 15.54% cases were due to Auto rickshaw/ van, 8.78% were due to Bi-cycle, 9.46% others. Besides that, management was given according to requirements where surgical intervention required in most of the cases, 64.87%, whereas Intensive care unit (ICU) support was required only 6.08 % cases, referred cases 8.11%, Patient refused to take treatment 10.13% cases. Conclusion: From our study we can say that, soft tissue injury (Abrasion/ Bruise/ Laceration) was a common injury found in road traffic accident patients, where CNG Auto-rickshaw and Motorcycle was the prominent source of road accident at this area, may be due to these are the main transportation in this rural area. Moreover, the recommendations from the world report on road traffic injury prevention should be considered and promptly implemented. The awareness among both users of road and administrators about road travel discipline should be very high in order to curb the ever-rising epidemic of road traffic accidents. KYAMC Journal Vol. 13, No. 01, April 2022: 41-44